2019
DOI: 10.3847/2041-8213/ab0f29
|View full text |Cite
|
Sign up to set email alerts
|

High-drag Interstellar Objects and Galactic Dynamical Streams

Abstract: The nature of 1I/'Oumuamua (henceforth, 1I), the first interstellar object known to pass through the solar system, remains mysterious. Feng & Jones noted that the incoming 1I velocity vector "at infinity" (v ∞ ) is close to the motion of the Pleiades dynamical stream (or Local Association), and suggested that 1I is a young object ejected from a star in that stream. Micheli et al. subsequently detected non-gravitational acceleration in the 1I trajectory; this acceleration would not be unusual in an active comet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…As MCs form and dissolve throughout the Milky Way, this could result in a rather inhomogeneous ISO concentration in the ISM, on timescales of several tens of Myr. This mechanism is independent of requiring substantial populations of low-area-density ISOs, in contrast to the process to concentrate ISOs in stellar streams proposed by Eubanks (2019). With inhomogeneity in play, the question arises of how typical the local ISO concentration that we measure with surveys in the Solar System is for the entire Galaxy (see also Pfalzner et al (2020)).…”
Section: Consequencesmentioning
confidence: 82%
“…As MCs form and dissolve throughout the Milky Way, this could result in a rather inhomogeneous ISO concentration in the ISM, on timescales of several tens of Myr. This mechanism is independent of requiring substantial populations of low-area-density ISOs, in contrast to the process to concentrate ISOs in stellar streams proposed by Eubanks (2019). With inhomogeneity in play, the question arises of how typical the local ISO concentration that we measure with surveys in the Solar System is for the entire Galaxy (see also Pfalzner et al (2020)).…”
Section: Consequencesmentioning
confidence: 82%
“…The scientific interest of these anterior discoveries are mainly to contribute to the statistics of ISOs and to assess their frequency in time. Indeed, galactic tides may change their apparition frequency in the Solar System (Eubanks 2019). For instance, Siraj & Loeb (2020) showed that they may present a directional asymmetry leading a better understanding of planetary system origin and nature.…”
Section: Interstellar Objectsmentioning
confidence: 99%
“…The stream velocity estimates are from [Kushniruk et al, 2017], supplemented by [Chereul et al, 1998, Liang et al, 2017, Gaia Collaboration et al, 2018. The 1I and LSR velocites are as shown in [Eubanks, 2019b], and the 2I velocity estimate is from the ephemeris of Bill Grey / Project Pluto.…”
Section: Dynamical Streams As Proxies For Iso Birth Systemsmentioning
confidence: 99%
“…(1) indicating these objects may pass through the inner solar system more or less continuously and that targeted searches [Eubanks, 2019b] or more sensitive survey instruments such as the VRT [Trilling et al, 2017] may be able to find numerous targets for future missions.…”
Section: Introductionmentioning
confidence: 99%